Seasonal patterns in nest survival of a subtropical wading bird, the Hawaiian Stilt (Himantopus mexicanus knudseni) - Harmon,Kristen C.; Wehr,Nathaniel H.; Price,Melissa R. (PeerJ, 2021)
Nest survival is influenced by where and when birds decide to breed. For ground-nesting species, nest-site characteristics, such as vegetation height and proximity to water, may impact the likelihood of nest flooding or depredation. Further, habitat characteristics, and thus nest survival, may fluctuate across the breeding season. The Hawaiian Stilt (‘Ae‘o; Himantopus mexicanus knudseni) is an endangered Hawaiian waterbird that nests in wetlands across the Hawaiian Islands. In this study, we used observational surveys and nest cameras to examine the impact of nest-site characteristics and day of nesting season on nest survival of the Hawaiian Stilt. Early nests had a higher chance of survival than late nests. For most of the nesting season, taller vegetation was correlated with increased nest survival, while shorter vegetation was correlated with increased nest survival late in the nesting season. Seasonal patterns in nest survival may be due to changes in parental behavior or predator activity. Nest depredation was responsible for 55% of confirmed nest failures and introduced mammals were the primary nest predators. Our study is the first to examine seasonality in nest survival of Hawaiian Stilts and suggests that, despite longer nesting seasons and year-round occupation of wetlands, late nesters in subtropical regions may have lower nest survival than early nesters, similar to trends observed in temperate regions.
Keywords: Seasonality; Introduced predators; Nest survival; Vegetation; Proximity to water